2012
DOI: 10.1007/s13187-012-0353-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing Partnerships and Recruiting Dyads for a Prostate Cancer Informed Decision Making Program: Lessons Learned From a Community-Academic-Clinical Team

Abstract: Prostate cancer (PrCA) is the most commonly diagnosed non-skin cancer among men. PrCA mortality in African-American (AA) men in South Carolina is ~50% higher than for AAs in the U.S as a whole. AA men also have low rates of participation in cancer research. This paper describes partnership development and recruitment efforts of a Community-Academic-Clinical research team for a PrCA education intervention with AA men and women that was designed to address the discordance between high rates of PrCA mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…This National Cancer Institute (NCI)-funded pilot program was delivered within an AA community from 2011-2014 and was in response to the U54 Request for Applications (RFA-CA-09-032) for Community Networks Program Centers to propose a research program of innovative and evidence-based clinical research adhering to the principles of community-based participatory research (CBPR) [8, 9, 19, 20] Additional requirements for the pilot program included: collaborations with other NCI-sponsored clinical trials, collaborations with other NCI-sponsored resources/programs [e.g., the NCI Community Clinical Oncology Program (CCOP), the NCI Community Cancer Centers Program (NCCCP)], and promoting the role of racial/ethnic and other underserved populations in research [8]. In keeping with CBPR principles, a community advisory panel of AA men and women was established at the beginning of the program to help guide all recruitment and project implementation and evaluation activities [8, 21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This National Cancer Institute (NCI)-funded pilot program was delivered within an AA community from 2011-2014 and was in response to the U54 Request for Applications (RFA-CA-09-032) for Community Networks Program Centers to propose a research program of innovative and evidence-based clinical research adhering to the principles of community-based participatory research (CBPR) [8, 9, 19, 20] Additional requirements for the pilot program included: collaborations with other NCI-sponsored clinical trials, collaborations with other NCI-sponsored resources/programs [e.g., the NCI Community Clinical Oncology Program (CCOP), the NCI Community Cancer Centers Program (NCCCP)], and promoting the role of racial/ethnic and other underserved populations in research [8]. In keeping with CBPR principles, a community advisory panel of AA men and women was established at the beginning of the program to help guide all recruitment and project implementation and evaluation activities [8, 21].…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with CBPR principles, a community advisory panel of AA men and women was established at the beginning of the program to help guide all recruitment and project implementation and evaluation activities [8, 21]. The original program was developed based on input from 81 focus group participants during a formative research phase [8, 9, 19, 20]. Education topics include “Overcoming barriers to discussing cancer” and “Prostate cancer screening guidelines: Should I get screened for prostate cancer?”.…”
Section: Introductionmentioning
confidence: 99%
“…The specific aims of this mixed methods research were to assess, among AAs in a faith-based setting: 1) the current knowledge and attitudes regarding PrCA prevention and screening, and participation in PrCA research (ie, discovery); 2) changes in knowledge and attitudes about research participation following a pilot education program developed based on informational needs (ie, development and delivery); and 3) culturally appropriate strategies for promoting cancer research among AAs in a faith-based community (ie, dissemination). 18,19 We discovered that AA men and women had limited knowledge about PrCA and limited experience participating in research. AA men and women had similar views on the barriers that limited PrCA communication (eg, fear), but had slightly different perspectives on which barriers had greater impact on AA men's informed decision-making about PrCA screening.…”
Section: Informed Prostate Cancer Screening -Owens Et Almentioning
confidence: 99%
“…The first two projects detailed below (ie, Photovoice and Teleconference) were completed as a part of the larger NCI-funded pilot project. 18 The third and fourth projects (ie, Decision Aid & Algorithm) were implemented as independent studies.…”
Section: Technology For Assessing and Aiding Health Decisionmaking Bementioning
confidence: 99%
“…There are several examples in the literature of "how to" build a Community-Academic Partnership (CAP) [9][10][11][12][13][14][15][16][17], but developing effective CAPs is challenging [18], and the steps to build and sustain these CAPs have not been well documented. Most reports of CAPs have instead focused on discussing accomplishments [19][20][21][22], while a few studies have reported on selected elements of successful collaborations, such as building trust and team-building activities [23,24]. There is a clear need for a better understanding of possible effective strategies [1].…”
Section: Introductionmentioning
confidence: 99%